Plant community data collected by Robert H. Whittaker in the Siskiyou Mountains, Oregon and California, USA. Issue 9 (4th July 2022) - Whittaker, Robert H.; Damschen, Ellen I.; Harrison, Susan
Abstract: In 1949–1951, ecologist Robert H. Whittaker sampled plant community composition at 470 sites in the Siskiyou Mountains (Oregon and California; also known as Klamath or Klamath‐Siskiyou Mountains). His primary goal was to develop methods to quantify plant community variation across environmental gradients, following on his seminal work challenging communities as discrete entities. He selected the Siskiyous because of their diverse and endemic‐rich flora, which he attributed to geological complexity and an ancient stable climate. He chose sites to span gradients of topography, elevation, geologic substrate, and distance from the coast. He used the frequencies of indicator species in his data to assign sampling locations to positions on the topographic gradient, nested within the elevational and substrate gradients. He originated in this study the concept of diversity partitioning, in which gamma diversity (species richness of a community) equals alpha diversity (species richness in homogeneous sites) times beta diversity (species turnover among sites along gradients). Diversity partitioning subsequently became highly influential and new developments on it continue. Whittaker published his Siskiyou work covering paleohistory, biogeography, floristics, vegetation, gradient analysis, and diversity partitioning in Ecological Monographs in 1960. Discussed in 2 pages of his 60‐page monograph, diversity partitioning accounts for >95% of its current >4300 citations. In 2006, we retrieved Whittaker's Siskiyou data in hard copy from the Cornell University archives and entered them in a database. We used these data for multiple published analyses, including some based on (re)sampling the approximate locations of a subset of his sites. Because of the continued interest in diversity partitioning and in historic data sets, here we present his data, including 359 sampling locations and their descriptors and, for each sample, a list of species with their estimated percent cover (herbs and shrubs) and numbers by diameter at breast height (DBH) category (trees). Site descriptors include the approximate location (road, trail, or stream), elevation, topographic aspect, geologic substrate (serpentine, gabbro, or diorite), and dominant woody vegetation of each location. For 111 sites, including the small number chosen to represent the distance‐to‐coast gradient, we could not locate his data. There are no copyright restrictions and users of these data should cite this data paper in any publications that result from its use. The authors are available for consultations about and collaborations involving the data.